Place Attachment Dan Loyalitas Wisatawan: Suatu Tinjauan Literatur - Maya Dewi Savitri (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The aim of this literature review is to enrich current knowledge about place attachment and tourist loyalty by theoretically reviewing previous research on these variables. Tourist loyalty is a tourist's willingness to revisit a destination and their willingness to recommend that destination to others. Place attachment is a person's bond with a place. Place attachment includes twoo dimensions, place identification, and place dependence. The results of this literature review found that place attachment have a direct and indirect influence (mediator) on tourist loyalty. The implication of this study suggest that tourism managers should understand place attachment as a complex psychological (cognitive, affective and behavioral) process in determining tourist loyalty.